A COMPARATIVE STUDY OF SAFETY FACTOR AND STRENGTH FACTOR IN UNDERGROUND MINE PILLARS USING NUMERICAL MODELING BASED ON MOHR-COULOMB CRITERIA - Putra Rosadi, Aslammabad
Underground mine pillars play a crucial role in ensuring the stability of the mine and the safety of workers. Pillar failure can lead to catastrophic collapses, endangering lives, causing economic losses, and harming the environment. This research aims to analyze the comparison between the Safety Factor and Strength Factor in underground mine pillars using numerical modeling based on the Mohr- Coulomb criterion. The modeling was conducted using RS2 software at various width-to-height ratios to evaluate whether the rock strength factor can represent the safety factor. The outcome of this research is to ensure whether the Strength Factor can effectively represent the value of the Safety Factor. The findings indicate a correlation between these two factors, where variations in the W/H ratio influence the resulting values. This study provides important insights for safer and more efficient pillar design in underground mining operations.